Kontribusi Pemikiran Ekonomi Islam pada Masa Daulah Saljuk: Telaah Terhadap Nizâm al-Mulk dan Imam al-Ghazali - Tacong, Hamzah; Haeriyah, Hamzah (JSE: Jurnal Sharia Economica, 2025)
The Seljuk Empire was an important political entity in Islamic history that not only excelled in the military field, but also played a major role in the development of Islamic science and economics. Figures such as Nizâm al-Mulk and Imam al-Ghazali made significant contributions in formulating Islamic economic concepts that are full of values ​​of justice, ethics, and maqâshid shari'ah. This article aims to trace the history of the Seljuk Empire, examine the economic system implemented, and explore the economic thoughts of these two important figures in the context of Islamic economic development. The method used is a literature study with a descriptive-analytical approach. The results of the study show that Seljuk economic thought, especially by Nizâm al-Mulk and Imam al-Ghazali, provides a strong foundation for modern Islamic economics, especially in terms of fiscal governance, market ethics, and social justice orientation.